2009
DOI: 10.1111/j.1365-3156.2009.02259.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced morbidity and mortality in the first year after initiating highly active anti‐retroviral therapy (HAART) among Ugandan adults

Abstract: Summaryobjective To evaluate the effect of highly active anti-retroviral therapy (HAART) and cotrimoxazole prophylaxis on morbidity after HAART eligibility.methods Between 1999 and 2006, we collected morbidity data from a community-based cohort of HAART-eligible patients, comparing patients initiating HAART and those non-HAART. Patients aged 15 years or older visited the clinic every 6 months and when ill. Baseline data on patients' characteristics, WHO stage, haemoglobin and CD4+ T-cell counts, along with fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 34 publications
3
20
0
1
Order By: Relevance
“…Of the nine, seven reported an estimate for the effect of cotrimoxazole on mortality, [28][29][30][31][32][33][34] whereas three reported an estimate for the effect on morbidity. 28,35,36 Two studies also reported the preventive effect on malaria. 28,36 Assessment of publication bias indicated that three studies [28][29][30] were of high methodological quality, while the other six [31][32][33][34][35][36] were of moderate methodological quality (Table 4, available at: http://www.who.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the nine, seven reported an estimate for the effect of cotrimoxazole on mortality, [28][29][30][31][32][33][34] whereas three reported an estimate for the effect on morbidity. 28,35,36 Two studies also reported the preventive effect on malaria. 28,36 Assessment of publication bias indicated that three studies [28][29][30] were of high methodological quality, while the other six [31][32][33][34][35][36] were of moderate methodological quality (Table 4, available at: http://www.who.…”
Section: Resultsmentioning
confidence: 99%
“…28,35,36 Two studies also reported the preventive effect on malaria. 28,36 Assessment of publication bias indicated that three studies [28][29][30] were of high methodological quality, while the other six [31][32][33][34][35][36] were of moderate methodological quality (Table 4, available at: http://www.who. int/bulletin/volumes/90/2/11-093260).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Historically, HIV/AIDS infection has been associated with many opportunistic malignancies such as Kaposi's sarcoma; however, since the introduction of highly active antiretroviral therapy (HAART), the incidence of opportunist neoplasm in this population has decreased, along with an increase in life expectancy (7). As a result, the incident of non-AIDSdefining-malignancy (NADM) has increased.…”
Section: Introductionmentioning
confidence: 99%